ChemInform Abstract: Pd‐Catalyzed Tandem Chemoselective Synthesis of 2‐Arylbenzofurans Using Threefold Arylating Triarylbismuth Reagents. Issue 24 (23rd May 2013) - Rao, Maddali L. N.; Jadhav, Deepak N.; Dasgupta, Priyabrata
Abstract This one‐pot tandem process obviates the use of preformed 2‐halobenzofurans to give 2‐arylbenzofurans.